La psicoterapia in un servizio per disturbi del comportamento alimentare - Aliquò, Maria Chiara (Il sogno della farfalla, 2020)
The aim of this paper is to propose and discuss a psychiatric practice carried on in Italian mental health services and conceived as a psychodynamic psychotherapy. The author analyzes how the practice has been conducted with the methodology based on the Human Birth Theory formulated by Massimo Fagioli. This represents an organic scientific theory which formulates a healthy birth and development and at the same time the possibility to treat mental illness through the cure of human mental reality. The article highlights on one hand what could be the contrasting elements in relation to the setting and organization of public mental health services and on the other what is the enormous potential and resources offered by the National Health Service. These could allow to restore social, political and cultural value to psychiatric and psychotherapeutic practice.